A new Aceria species (Acari: Eriophyoidea) on Echinops ritro L. subsp. ruthenicus (M.Bieb.) Nyman (Asteraceae) from Serbia and a supplement to the original description of Aceria brevicincta (Nalepa 1898) - Vidović, Biljana (Zootaxa, 2011)
A new species of eriophyoid mite, Aceria banatica n. sp. inhabiting Echinops ritro L. subsp. ruthenicus (M.Bieb.) Nyman has been described from Serbia. A comparison of characters between A. banatica n. sp. and Aceria echinopsi Boczek and Nuzzaci 1988, the only other species known from Echinops sp., is given. A supplementary description of Aceria brevicincta (Nalepa 1898) found on Jurinea mollis (L.) Rchb. in Serbia is included along with a comparison of taxonomic characters of this population with previously described specimens from Hungary and the poor original description from Austria.